Current situation and future prospects for beef production in Thailand - A review - Thanaporn Bunmee (2018)
© 2018 by Asian-Australasian Journal of Animal Sciences. Thailand is a country of native beef cattle resource farming. It has undergone rapid social and economic change in the past decade. Agricultural growth has been maintained by increasing the production of rice and cassava. Changing economic status also provides opportunities for beef cattle producers to meet increasing consumer demand for beef. Finishing beef cattle numbers in Thailand were about 1.0 M head in 2015. Beef produced in Thailand has exclusively been for domestic consumption. Only 1% of Thailand's beef cattle are for the premium market which is based on marbling score, 40% are sold into modern markets that consider muscling of cattle, and the remainder enter traditional markets. Cross-bred cattle for the premium market are raised within intensive systems. Most producers of premium beef are members of beef cooperatives, or have invested in their enterprises at high levels. Culled cow (native or cross-bred cattle) are mainly for small holder farm production. Malaysia, Indonesia, and other members of the Asian Economic Community (AEC) are set to become the largest beef market, which has been confirmed by 2015 through 2020 forecasts for consumption of beef that must increasingly be halal. These circumstances are likely to be challenging for beef producers in Thailand to gain a share of this market. Integration across all sectors involved in beef production in Thailand will be required.